2020
DOI: 10.3389/fmed.2020.00485
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognosis of 218 Patients With COVID-19: A Retrospective Study Based on Clinical Classification

Abstract: Background: Coronavirus disease 2019 (COVID-19) is an emerging infectious disease that has spread worldwide. Methods: This was a retrospective case series involving 218 patients admitted to three tertiary hospitals in the Loudi, Shaoyang, and Xiangtan areas of China from January 21 to June 27, 2020, who were confirmed by RT-PCR to have SARS-CoV-2. The patients' clinical characteristics, laboratory results, treatments, and prognoses based on clinical classification were recorded. Poor outcome was defined as adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
2
25
1
3
Order By: Relevance
“…The patients with more severe disease course had higher temperature, lower blood oxygen saturation, lower eosinophils count, higher ESR, higher CRP and creatinine levels, lower GFR, and higher levels of LDH and troponin T on admission to the hospital than patients with milder disease course. In general, these results concur with previous studies [1, 5, 6, 7, 8, 11]. However, some findings should be discussed in greater detail.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The patients with more severe disease course had higher temperature, lower blood oxygen saturation, lower eosinophils count, higher ESR, higher CRP and creatinine levels, lower GFR, and higher levels of LDH and troponin T on admission to the hospital than patients with milder disease course. In general, these results concur with previous studies [1, 5, 6, 7, 8, 11]. However, some findings should be discussed in greater detail.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also demonstrated the relationship between COVID-19 severity and reduced renal function. It contrasts with Feng et al [1] and Yan X. et al [11], who revealed no differences in this function. In our study, the level of creatinine was significantly higher in the group with severe disease course than in groups with mild or moderate disease course.…”
Section: Discussioncontrasting
confidence: 76%
“…The 136 studies, which involved 102,345 patients, included 97 observational studies, 11 case series, five letters, one application note, 13 randomized trials, one pilot study, five reports, one non-randomized trial, one short communication, and one correspondence. The countries involved in these studies included China (51 studies ( Cai et al, 2020 ; Cao et al, 2020a ; Cao et al, 2020b ; Chen et al, 2020a ; Chen et al, 2020b ; Chen et al, 2020c ; Chen et al, 2020d ; Chen Jun et al, 2020 ; Deng et al, 2020 ; Hu et al, 2020a ; Hu et al, 2020b ; Huang et al, 2020a ; Huang et al, 2020b ; Huang et al, 2020c ; Hung et al, 2020 ; Jiang et al, 2020 ; Li et al, 2020a ; Li et al, 2020b ; Lian et al, 2020a ; Lian et al, 2020b ; Liu et al, 2020a ; Liu et al, 2020b ; Liu et al, 2020c ; Liu et al, 2020d ; Mo et al, 2020 ; Ouyang et al, 2020 ; Pan et al, 2020 ; Shi et al, 2020 ; Tang et al, 2020 ; Wang et al, 2020a ; Wang et al, 2020b ; Wang et al, 2020d ; Wang et al, 2020e ; Wu et al, 2020a ; Wu et al, 2020b ; Wu et al, 2020c ; Xu et al, 2020a ; Xu et al, 2020b ; Xu et al, 2020c ; Yan et al, 2020a ; Yan et al, 2020b ; Yang et al, 2020 ; Yu et al, 2020a ; Yu et al, 2020b ; Zhang et al, 2020a ; Zhang et al, 2020b ; Zhang et al, 2020c ; Zhao et al, 2020 ; Zheng et al, 2020 ; Zhou et al, 2020 ; Zhu et al, 2020 )), the United States (31 studies ( Alam et al, 2020 ; Bhatraj...…”
Section: Resultsmentioning
confidence: 99%
“…We used the general term “relative risk” to refer to the mortality risk. A total of 16 observational studies ( Berenguer et al, 2020 ; Cao et al, 2020b ; Catteau et al, 2020 ; Ferrando et al, 2020 ; Gupta et al, 2020 ; Krishnan et al, 2020 ; Lee et al, 2020a ; Morrison et al, 2020 ; Nowak et al, 2020 ; Okoh et al, 2020 ; Primmaz et al, 2020 ; Salacup et al, 2020 ; Wang et al, 2020a ; Yan et al, 2020b ; Zerah et al, 2020 ; Zhou et al, 2020 ) were involved in this assessment. We extracted the number of patients who died from COVID-19 following a certain treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical course of the COVID-19 is highly variable, ranging from asymptomatic infection to respiratory failure, multi-organ dysfunction, and mortality. Apart from the respiratory system, COVID-19 is also associated with hazardous effects on other body systems [1,2]. Several studies have underlined that older patients and patients with comorbidities are more susceptible to COVID-19, its more serious complications, and progression to severe disease.…”
Section: Introductionmentioning
confidence: 99%